Coverage and determinants of infant postnatal care in Nigeria: A population‐based cross‐sectional study - Bolaji Emmanuel Egbewale; Olusola Oyedeji; Jesse Bump; Christopher Robert Sudfeld (Wiley, 2024)
ABSTRACT Importance In 2019, Nigeria had the largest number of under‐5 child deaths globally and many of these deaths occurred within the first week of life. The World Health Organization recommends infant postnatal care (PNC) attendance to support newborn survival; however, utilization of PNC is known to be low in many contexts. Objective This study examined coverage and individual‐level determinants of infant PNC attendance in Nigeria. Methods Nigeria Demographic Health Survey (NDHS) 2018 data were used to evaluate infant PNC coverage and determinants. Infant PNC was defined as receipt of care within 2 days of birth. Children delivered up to 2 years before the 2018 NDHS were included. We examined predictors of infant PNC with modified Poisson regression models to estimate relative risks (RRs). Results The national coverage of infant PNC was 37.3% (95% confidence interval [CI]: 35.8%-38.7%). Significant heterogeneity in PNC attendance existed at state and regional levels. Facility delivery was strongly associated with the uptake of PNC (RR: 6.07; 95% CI: 5.60-6.58). Greater maternal education, maternal employment, urban residence, female head of household, and greater wealth were also associated with an increased likelihood of PNC visits. Interpretation The uptake of infant PNC is low and interventions are urgently needed to promote equity in access and increase demand for PNC in Nigeria.